Project Management for Strengthening the Pancasila Student Profile - Margiyati; Rambat Nur Sasongko; Manap Somantri (International Journal of Innovation and Education Research, 2023)
This research design aims to find out how the project management of strengthening the student profile of Pancasila as an implementation of the “kurikulum merdeka” at SDIT Uswatun Hasanah Padang Jaya. This research uses a qualitative approach with a case study. This research includes descriptive analysis, case study. The subjects in this study were 5 people, namely: 1) Principal, 2) Vice principal for curriculum affairs, 3) Classroom teacher, 4) Mupel teacher and 5) Students of SDIT Uswatun Hasanah Padang Jaya. Various techniques were used to collect data and information. They are: (1) interviews, (2) observations, and (3) documentation studies. In accordance with the method, the research instruments used are as follows: 1) interview method, the instrument is an interview guideline; 2) observation, the instrument is a check list; 3) documentation, the instrument is a documentation guideline. Based on the research that has been conducted, it shows that the management of the art performance project at SDIT Uswatun Hasanah can foster the character of the Pancasila learner profile and the creativity of students in performing their art as an implementation of the “kurikulum merdeka”.